KONTEKSTUALISASI KETELADANAN SOSIAL RASULULLAH DI ZAMAN KIWARI - Abu Maskur (An-Nufus, 2020)
This paper discusses the concept of the social example of the Prophet Muhammad, which can be used as guidelines and guidance in living a life full of challenges due to the negative impacts of the era of massive industrialization and globalization. One of the negative impacts is that we can see in some religious and political figures whose behavior does not reflect exemplary behavior, such as speaking harshly, insulting and sometimes - not being reluctant - to insult others who are different from him. Ironically, if the religious figure is a Muslim, and the political figure comes from an "Islamic" party. For that, we need to look back at the lifestyle of the Prophet Muhammad as a compass to move and inspire many people. Moreover, this has been emphasized by Alquan that in the Prophet there is a good role model. Among the social examples of the Messenger of Allah are being fair, gentle, humanist and tolerant. By doing so, it is hoped that the negative impact of industrialization and capitalization in this modern era on social life, including the social life of Muslims, can be reduced. This paper uses a literature study approach to analyze the problems discussed. The findings in this research include the very relevant concepts and social teachings of the Prophet. In addition, several Islamic methods in term of social exemplary lwere found to achieve this.